Retention of functional mitochondria in mature red blood cells from patients with sickle cell disease. (7th June 2022) - Moriconi, Chiara; Dzieciatkowska, Monika; Roy, Micaela; D'Alessandro, Angelo; Roingeard, Philippe; Lee, June Young; Gibb, David R.; Tredicine, Maria; McGill, Marlon A.; Qiu, Annie; La Carpia, Francesca; Francis, Richard O.; et al.
Summary: Sickle cell disease (SCD) is an inherited blood disorder characterized by sickled red blood cells (RBCs), which are more sensitive to haemolysis and can contribute to disease pathophysiology. Although treatment of SCD can include RBC transfusion, patients with SCD have high rates of alloimmunization. We hypothesized that RBCs from patients with SCD have functionally active mitochondria and can elicit a type 1 interferon response. We evaluated blood samples from more than 100 patients with SCD and found elevated frequencies of mitochondria in reticulocytes and mature RBCs, as compared to healthy blood donors. The presence of mitochondria in mature RBCs was confirmed by flow cytometry, electron microscopy, and proteomic analysis. The mitochondria in mature RBCs were metabolically competent, as determined by enzymatic activities and elevated levels of mitochondria‐derived metabolites. Metabolically‐active mitochondria in RBCs may increase oxidative stress, which could facilitate and/or exacerbate SCD complications. Coculture of mitochondria‐positive RBCs with neutrophils induced production of type 1 interferons, which are known to increase RBC alloimmunization rates. These data demonstrate that mitochondria retained in mature RBCs are functional and can elicit immune responses, suggesting that inappropriate retention of mitochondria in RBCs may play an underappreciated role in SCD complications and be an RBC alloimmunization risk factor.